Ensino de ciências no contexto da Lei nº 10.639/2003 em tempos de pandemia do covid-19 - Valeriana Christina de Melo e Sousa (2021)
Based on law nbr 10639/2003, which declares that teaching Afro-Brazilian Culture and History is mandatory in both public and private elementary and high schools, this research is in line with actions that aim to strengthen the perspective of a scientific education that involves ethnic-racial relationships. Its objective is to propose possibilities for sharing ideas, doubts, and to establish discernment between teachers and basic education students regarding sciences in an anti-racist perspective that is committed to ethnic-racial relationships. To this end, the activities proposed were elaborated for Science students in the third cycle of middle-school regarding the representativeness of black women in science, a reflection on racism and scientific production and viruses, emphasizing Sars cov-2, since this paper is being developed in the context of the covid-19 pandemic. As the result of a Workshop directed at Science teachers from the third cycle/middle school (Fundamental II) of the municipal school district of Belo Horizonte, we carried out three, two-hour online meetings, attending the recommendations made by the World Health Organization, regarding social distancing in order to combat and control contamination by the coronavirus. These meetings were recorded and the dialogues transcribed and analyzed in order to check the perspectives of the participants in relation to the themes that were discussed, as well as their contributions toward the proposed activities. Subsequently, interviews were held with two teachers who had participated in the workshop in order to obtain a more detailed understanding of their personal and learning experiences as black women with graduate/post-graduate degrees in the area of Science and their academic practices, resulting from the construction of their own identities. From this research, it was observed that the teachers´ suggestions for the activities involved pedagogical postulations, accounts of experiences, materials and methodologies that allowed the enhancement of the sequence of lessons presented at the workshop. Whereas, the ideas highlighted in the teachers´ discourses were the stereotyped vision of white and Eurocentric science, the challenges of relating the teaching of science to racial themes, the mistaken biological concept of race, and the social and historical effects that this implies, as well as the difficulty to obtain a group effort with teachers of other subjects in this regard. From these results and the researcher´s own experiences, three metatexts were elaborated, following the perspective of the “Análise Textual Discursiva” - Moraes e Galiazzi (2004) (Discursive Textual Analysis by Moraes and Galiazzi, 2004), in order to develop the constructions created by the participants of this research during the workshop, through interviews and literature studies. As a result of this work, we developed material for Science teachers with a proposal of activities aimed at Fundamental II, in order to promote an anti-racist education, as well as formative and informative texts regarding strategies and other topics to be broached in these practices, in conjunction with the national curricular directives of Law 10639/03, “Educação das Relações Étnico Raciais e para o Ensino de História e Cultura Afro-Brasileira e Africana” (BRASIL, 2006) (Education of Ethnic-Racial Relations and for Teaching Afro-Brazilian Culture and History). We believe that this work and its outcome can contribute toward basic education and toward training Science teachers to combat structural racism, through the construction of more humane and egalitarian educational endeavors.